Analisis Financial Distress Menggunakan Metode Altman Z-Score Untuk Memprediksi Kebangkrutan Pada Sektor Infrastructures Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2019-2024 - Kezia Khairani; Hasudungan Pangaribuan (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the condition of financial distress and predict the potential bankruptcy of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. The analytical method used in this study is the Altman Z-Score method, which combines five financial ratios, namely Working Capital to Total Assets (WCTA), Retained Earnings to Total Assets (RETA), Earnings Before Interest and Taxes to Total Assets (EBITTA), Market Value of Equity to Total Liabilities (MVETL), and Sales to Total Assets (STA). This type of research is quantitative descriptive research using secondary data in the form of company annual financial reports. The research sample consists of five companies: IBST, WSKT, META, TGRA, and ADHI. The results of this study indicate that IBST, WSKT, TGRA, and ADHi have a Z value <1.8, meaning they are in the Distress Zone category, and META has a value of 1.8 <Z <2.99, meaning they are in the Grey Area category. This indicates that some infrastructure sector companies are in the distress zone category, while other companies are in the grey area condition. This finding indicates differences in the level of financial health between companies, so that financial distress analysis is important as a basis for decision making for management, investors, and creditors